High Urine Albumin-to-Creatinine Ratio is Associated with Increased Arterial Stiffness in Diabetes: A Chinese Cross-Sectional Study - Guo K; Zhu Y; Yu Q; Chen H; Cheng W; Zhang X; Zhang X; Liu B; Zhou Z; Kuang X (Diabetes, Metabolic Syndrome and Obesity, 2024)
Kai Guo,1,2 Yuqin Zhu,3 Qian Yu,4 Hong Chen,5 Wei Cheng,2 Xiaoyan Zhang,2 Xuelian Zhang,2 Biwen Liu,2 Zunhai Zhou,2 Xingya Kuang5 1School of Medicine, Tongji University, Shanghai, 200092, People’s Republic of China; 2Department of Endocrinology, Yangpu Hospital, School of Medicine, Tongji University, Shanghai, 200090, People’s Republic of China; 3Department of Emergency, Yangpu Hospital, School of Medicine, Tongji University, Shanghai, 200090, People’s Republic of China; 4Department of Dermatology, Shanghai Tenth People’s Hospital, School of Medicine, Tongji University, Shanghai, 200072, People’s Republic of China; 5Department of Occupational Medicine, Yangpu Hospital, School of Medicine, Tongji University, Shanghai, 200090, People’s Republic of ChinaCorrespondence: Xingya Kuang, Department of Occupational Medicine, Yangpu Hospital, School of Medicine, Tongji University, No. 1015, Hejian Road, Shanghai, 200090, People’s Republic of China, Tel +86-15021904362, Email kuangxingya@163.com Zunhai Zhou, Department of Endocrinology, Yangpu Hospital, School of Medicine, Tongji University, No. 450, Tengyue Road, Shanghai, 200090, People’s Republic of China, Tel +86-18001779479, Email zhouzunhai5008@163.comPurpose: Elevated urine albumin-to-creatinine ratio (UACR) is an established risk factor for microvascular disease in the general population. However, it is unclear whether UACR is associated with arterial stiffness in diabetes. We aimed to assess the relationship between UACR levels and the risk of arterial stiffness in patients with diabetes.Methods: From July 2021 to February 2023, a total of 1039 participants were assessed for the risk of arterial stiffness, which was evaluated by brachial-ankle pulse wave velocity (baPWV). The value of UACR≥ 30 mg/g was defined as high UACR. The UACR level had an abnormal distribution and was log2-transformed for analyses to reduce skewness and volatility. High baPWV was evaluated as categorical variables divided by the highest quartile of the values by sex. The relationship between UACR and arterial stiffness was analyzed by linear curve fitting analyses. Multiple logistic regression models were used to analyze the crude and adjusted odds ratio (OR) of UACR for high baPWV with 95% confidence interval (CI). In addition to applying non-adjusted and multivariate-adjusted models, interaction and stratified analyses were also carried out.Results: The baPWV level was significantly higher in the high UACR group compared with that in the normal UACR group (1861.84 ± 439.12 cm/s vs 1723.13 ± 399.63 cm/s, p< 0.001). Adjusted smoothed plots suggested that there are linear relationships between log2-transformed UACR and high baPWV, and Spearman correlation coefficient was 0.226 (0.176– 0.276, p< 0.001). The OR (95% CI) between log2-transformed UACR and high baPWV were 1.26 (1.19– 1.33, p< 0.001), and 1.16 (1.08– 1.25, p< 0.001) respectively in diabetic patients before and after adjusting for potential confounders.Conclusion: The elevated UACR was associated with arterial stiffness in Chinese patients with diabetes.Plain Language Summary: 1. The mean baPWV level was significantly higher in the high UACR group compared with that in the normal UACR group.2. The sex-specific hierarchical analysis revealed that baPWV levels and the incidence of high baPWV were significantly elevated with increased UACR.3. Curvilinear relationships between log2-transformed UACR and the risk of high baPWV.4. Positive association between UACR and high baPWV in patients with diabetes.Keywords: diabetic kidney disease, cardiovascular diseases, albuminuria, pulse wave velocity, biomarker, prognosis